Do this in remembrance of me : the disputed works in the Lukan Institution narrative (Luke 22: 19b-20) : an historico-exegetical, theological, and sociological analysis /: the disputed works in the Lukan Institution narrative (Luke 22: 19b-20) : an historico-exegetical, theological, and sociological analysis. (2006) - Unknown
No abstract available